Doing Experimental Media Archaeology Practice - van der Heijden, Tim (De Gruyter, 2022)
The hands-on and experimental approach of DEMA offers the unique opportunity to 'grasp' media and communication technologies in their concrete materiality and tangibility and to (re)-sensitize historians and communication scholars for the material qualities and performative dimension of past media devices and practices.